Academy of Joint Integrity offers training to the drinks industry. Issue 11 (November 2016) - Unknown
Abstract : The Academy of Joint Integrity, which is part of global sealing specialist Flexitallic, is training maintenance teams in the drinks industry by offering certified flange assembly/sealing technology courses to underpin safety in the distillery sector.